Prosopography of the Somatophylakes of Alexander the Great (2022)
Ancient authors such as Arrian, Polybius, Plutarch and several others have dedicated a huge amount of literature to the exploits and politics of Alexander the Great. Modern scholars, drawing from the narrations of ancient authors, have analysed several aspects of the times and life of this great leader and those of his Diadochi. However, little attention has been paid to the men who served as his bodyguards. This paper is therefore designed to examine the biographies of the somatophylakes of Alexander the Great, with a view to understanding their roles throughout the period of Alexander's warring years until his death in 323 BC, as well as their positions and influences post Alexander. The paper adopts a historical methodology as it examines the times and lives of the bodyguards. Plutarch's ideology on biography is adopted as framework. Further studies may examine the sphere of control of the Diadochi and their roles in promoting Hellenistic culture in Africa and the Near East after the demise of Alexander